(untitled) (Qawanin Jurnal Ilmu Hukum, 2021)
This study aims to determine the factors that cause a person to commit the crime of trafficking in persons, to determine the efforts made by law enforcement officials in this case, especially the Makassar Police to tackle the crime of trafficking in persons. This type of research is a descriptive empirical legal research. Using a qualitative legal research approach. The location of the legal research was carried out at the Polrestabes Makassar. Types and sources of legal research data include primary data and secondary data. Data collection techniques by interview and literature study. Based on the results of the research and discussion, it was concluded that the factors in the occurrence of the crime of trafficking in persons consisted of economic factors, socio-cultural environmental factors, individual factors, lack of public knowledge about the consequences of crime, and the lack of firmness in law enforcement officers in following up on criminal cases of trafficking in persons. Regarding efforts to tackle the criminal act of trafficking in persons, it consists of preventive and repressive measures. Namely by disseminating information to the public regarding the consequences of the crime of trafficking in persons and implementing Law Number 21 of 2007 concerning the eradication of the criminal act of trafficking in persons properly so as to provide a deterrent effect on the perpetrator and no longer repeat his actions.